Understanding contrast perception in amblyopia: a psychophysical analysis of the ON and OFF visual pathways - Wei, Junhan; Cheng, Ziyun; Kong, Deying; Lin, Wenman; Hess, Robert F.; Zhou, Jiawei; Reynaud, Alexandre (Frontiers in Psychology, 2024)
The study aimed to explore potential discrepancies in contrast sensitivity in the ON and OFF visual pathways among individuals with amblyopia compared to controls.: Eleven adult amblyopes (26.2 ± 4.4 [SD] years old) and ten controls (24.6 ± 0.8 years old) with normal or corrected to normal visual acuity (logMAR VA ≤ 0) participated in this study. Using the quick contrast sensitivity function (qCSF) algorithm, we measured balanced CSF which would stimulate the ON and OFF pathways unselectively, and CSFs for increments and decrements that would selectively stimulate the ON and OFF visual pathways. Contrast sensitivity and area under log contrast sensitivity function were extracted for statistical analysis.Results: For the balanced CSF, we found significant interocular differences in sensitivity and area under log contrast sensitivity function in both amblyopes (F [1,10] = 74.992, p < 0.001) and controls (F [1,9] = 35.6, p < 0.001), while such differences were more pronounced in amblyopes than in controls. For increment and decrement CSFs, we found that the increment sensitivity (p = 0.038) and area under log contrast sensitivity function (p = 0.001) were significantly lower than the decrement in the amblyopic eye. Such differences between increment and decrement CSFs were not observed in the fellow eye of the amblyopes or in the controls.There is a subtle difference in the contrast sensitivity of the amblyopic eye when exposed to stimulation in the ON and OFF pathways.